He puhuivat vain rahasta - Härkönen, Elina (Umeå universitet, 2023)
My work examines the controversy surrounding land ownership. In past years, I have encountered a few brutally clear-cut forests in my everyday life landscapes in Northern Finland. Te landscape has changed drastically. Suddenly, a large area of old forest has disappeared, leaving a barren gap in the middle of the forested hill. It has turned out that these lands are privately owned and then inherited by the next generation not living in the region. Te one and only motive for the clearcuts has been money growing in those trees. I started my art piece after experiencing the sorrow of the drastic loss of a forest I regularly visit. Te sight of the pile of cut-down trees was unbelievable. I had childishly believed that such an old forest, with its thick old tree trunks, would be left out of forest management. During the LiLa feldwork, we visited the Västerbotten museum where the Swedish Photographer Sune Jonsson’s exhibition touched on the same topic of ownership and the value of a landscape. Te name of my work refers to a statement in one of his interviews with local people living in remote areas that were the target of government reforms. Where is the real value of the land we say we own?